Banking and high-tech exports: Premises for long-term added value creation? - Dan Costin Nitescu; Valentin Murgu; Mariana Bunea (Amfiteatru Economic Journal, 2024)
The article addresses the issue of identifying some determinants regarding the growth of high-tech exports at the European level, as a starting point in the creation of long-term added value. In this study, the relationship between the endogenous variable high-tech exports and the exogenous variables: Research and Development Expenditure, Gross Capital Formation, Gross Domestic Product, Articles in scientific and technical journals, and Domestic credit to the private sector were examined. In the empirical study, econometric data analysis was used (by applying the FGLS model). A sample consisting of the 27 countries of the European Union was selected to identify the associations between the variables. The identified results revealed a positive impact of both Research and Development Expenditure and Gross Domestic Product on high-tech exports. Another statistically significant factor identified is Domestic credit to the private sector, but with reverse causality, with several countries with more domestic debt being less likely to perform well in the field.
Keywords: F10; O32; O52; 330; high-tech exports; value added; R&D expenditure; bank financing; Gross Domestic Product; innovations; European Union